Nitrous oxide inhalation combined with lidocaine local anesthesia on the comfort of plastic surgery outpatient procedures: a randomized, controlled, single-blind trial - Su, Yidan; Zou, Jiefeng; Guo, Jingwen; Qi, Yan; Li, Yonghua; Nie, Bing; Dong, Ziying; Zhang, Wenjun (Frontiers in Medicine, 2025)
BackgroundThe use of infiltration injection of lidocaine with adrenaline in outpatient plastic surgeries has certain limitations, such as injection pain, increased blood pressure, and heart rate fluctuations. Nitrous oxide has good analgesic and anti-anxiety effects. However, its application in outpatient plastic surgery is relatively limited. This study aimed to investigate the advances following combined nitrous oxide inhalation and local anesthesia to provide a new anesthesia option for improving surgical comfort.MethodsThis study adopted a randomized, single-blind grouping method. After the preoperative assessment, patients inhaled nitrous oxide (up to 50% concentration) or air through a nasal mask. Before and during surgery, the patients’ basic information and vital signs were recorded. Follow-up was performed three days after surgery.ResultsA total of 82 patients were randomized, with 41 in each group (Group A: N₂O/O₂; Group B: Air/O₂). Group A showed significantly better outcomes across multiple measures: maximum pain score was lower (1.9 ± 0.7 vs. 3.1 ± 0.9; mean difference: -1.2, 95% CI: −1.6 to −0.8; p = 0.0039), hemodynamic parameters were more stable, and anxiety reduction was greater (mean difference in BSTAI change: -0.6, 95% CI: −1.1 to −0.1; p = 0.018) compared to Group B.ConclusionThis combined anesthesia method significantly reduced the pain experienced during surgery, stabilized blood pressure and heart rate, reduced anxiety, and improved surgical comfort in outpatient plastic surgery patients.Clinical trial registrationClinicaltrials.gov, identifier ChiCTR2400080612.